English composition as a happening - Sirc, Geoffrey Michael (Utah State University Press, 2002)
What happened to the bold, kicky promise of writing instruction in the 1960s? The current conservative trend in composition is analyzed allegorically by Geoffrey Sirc in this book-length homage to Charles Deemer's 1967 article, in which the theories and practices of Happenings artists (multi-disciplinary performance pioneers) were used to invigorate college writing.